Empowerment of the Sanggang Village Community Through Training on Coconut Sap Processing and Making Ant Sugar-Based Sponge - Novian Wely Asmoro; Sri Hartati; Bovi Wira Harsanto (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Sanggang Village is one of the areas where dwarf coconuts are widely planted, managed by the Karya Makmur farmer group (gapoktan). The young coconut trees can be tapped for sap, which can then be processed into palm sugar as an alternative to granulated sugar. However, the farmer group in Sanggang Village still does not understand the potential of coconut sap and its processing. Therefore, the purpose of this community service is to provide understanding and competency to the farmer group in Sanggang Village regarding the development of dwarf coconut sap processing. The target group of the team is the Karya Makmur farmer group, which is responsible for the maintenance and processing of dwarf coconuts. The methods used by the team are training (socialization and practice), application of technology on tapping coconut sap and processing it into palm sugar using several evaluation instruments, such as pre-tests and post-tests, visual observations, and community testimonials. The results of the community service activities show an 80% increase in community understanding regarding coconut sap processing and its economic potential. These results are accompanied by enthusiasm and increased community skills in processing palm sugar into derivative products in the form of cakes. This community service initiative has sparked enthusiasm and enthusiasm in processing and downstreaming dwarf coconuts, creating valuable products and, hopefully, providing a new source of income for the Sanggang Village community. This initiative has the potential to be developed and expanded into a palm sugar-based product marketing venture, which could be implemented in collaboration with the Village-Owned Enterprise (BUMDES) in Sanggang Village, specifically for the snack business. Keywords: Coconut Sap; Dwarf Coconut; Farmer Group; Palm Sugar; Sanggang Village